Creativity and Critique in Digital Learning and Teaching Insights for Learning Design in Business and Law - Baxter, Jacqueline; Selby-Fell, Helen; Gilbert, Andrew; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
(3z(BThis book shares valuable practice for how to navigate innovative approaches in digital education environments that are attainable for staff and accessible and engaging for students.(3y(B- Radka Newton, Director of Centre for Scholarship and Innovation in Management Education, Lancaster University Management School, UK (3z(BDigital scholarship is an area of growing importance and centrality. This book aims to inform and clarify foundational assumptions in learners and teachers, and to reduce the mismatch of expectations on all sides by the provision of considered and evidence-based scholarship.(3y (B- Caroline Strevens, Portsmouth Law School, University of Portsmouth, UK (3z(BThis volume is a major resource for anyone seeking to understand the challenges of contemporary police professionalisation.(3y(B- Tom Cockcroft, School of Law and Policing, University of Central Lancashire, UK This open access edited collection is aimed at educators, student services staff, and university management. It is timely in adopting a forward-facing view of various aspects of digital teaching and learning in business and law and provides a vital resource for those designing, managing or thinking about digital learning in both fields. Jacqueline Baxter is Professor of Public Leadership and Management, and founding Director of the Scholarship Centre for innovation in online Legal and Business education (SCiLAB) in the Faculty of Business and Law at The Open University, UK, which she led from 2019 to 2024. She is Fellow of the Academy of Social Sciences and Principal Fellow of the Higher Education Academy. Helen Selby-Fell holds a Senior Lectureship in Policing and is Deputy Director of SCiLAB in the Faculty of Business and Law at The Open University, UK. Andrew Gilbert is Senior Lecturer in Law and Associate Dean for Curriculum and Partnerships in the Faculty of Business and Law at The Open University, UK.s
Chapter 1. Where are we now with digital teaching? Critical reflections on digital teaching and SoTL in business and law -- Chapter 2. Every truth has two sides: the impact of ChatGPT on law and business education -- Chapter 3. Digital Poverty in the UK and its impact on higher education: a human rights approach -- Chapter 4. Investigating student engagement with digital interactive learning tools at level one: actual and perceived value of these resources -- Chapter 5. Teaching skills online in the BA in Business Studies -- Chapter 6. Police-academic partnerships: delivering the Police Constable Degree Apprenticeship -- Chapter 7. How to develop a sense of belonging in online distance learning? -- Chapter 8. Supporting care experienced students: piloting a project in the Faculty of Business and Law -- Chapter 9. Navigating the award gap of ethnic minority students -- Chapter 10 Designing digital law clinics for student success -- Chapter 11. An exploration of the use of reflective assessment by policing apprentices whilst in an operational setting -- Chapter 12. Simulation games in teaching operations and supply chain management -- Chapter 13. The futures of digital learning and teaching.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Educational technology; Art -- Study and teaching; Education -- Curricula; Business; Management science; Professional education; Vocational education; Digital Education and Educational Technology; Creativity and Arts Education; Curriculum Studies; Business and Management; Professional and Vocational Education